Risk Factors for Extended Spectrum Beta-Lactamase Producing Klebsiella pneumoniae in Arifin Achmad Hospital Riau, Indonesia (Majalah Kedokteran Bandung, 2024)
Multidrug-Resistant (MDR) bacteria that produce Extended-Spectrum Beta-Lactamase (ESBL) isolates pose a global threat to human health, including in Indonesia. The availability of therapeutic options for ESBL-producing Klebsiella pneumoniae (ESBL-KP) is limited, making early recognition of patients with ESBL crucial to preventing the spread of these bacteria within the hospital. This study aimed to examine the risk factors associated with ESBL-KP in the Arifin Achmad General Hospital Riau, Indonesia. This prospective case-control study was performed from January to March 2018, with the diagnosis of ESBL established using the Vitek 2 compact automated tool. The risk factors examined were gender, age, specimen type, ward of origin, hospitalization exceeding seven days, history of antibiotic usage, presence of diabetes mellitus, chronic kidney disease, immunocompromised status, ICU care, and hospitalization within the past month. Patients hospitalized for more than seven days were 4.75 times more likely to develop ESBL-KP, while immunocompromised patients were 2.92 times more likely to develop ESBL-KP. However, the history of antibiotic use, diabetes mellitus, chronic kidney disease, ICU care, and hospitalization within the past month did not exhibit statistically significant associations with ESBL-KP infection. Therefore, ESBL-KP infection should be anticipated in patients hospitalized for more than seven days and those who are immunocompromised. It is crucial to implement infection prevention and control measures, as well as selecting appropriate antibiotic therapy.
Keywords: Extended-Spectrum Beta-Lactamase (ESBL); Klebsiella pneumoniae; risk factors